Weed science at CIAT (Centro Internacional de Agricultura Tropica) and weed problems in Latin America - Doll, Jerry D. (Cambridge University Press, 1980)
Latin America is a region of contrasts including mountains and valleys, deserts and jungles, forests and prairies, prosperous and poor, modern and traditional, small farms and huge ones, malnourished and well-fed, machines and manpower, herbicides and machetes. Any country from Mexico to Chile would provide examples of these contrasts. The countries share a common heritage of language, culture, religion, and education. Each is unique in its present developmental stage and future plans (6).